Impact of Chronic Viral Infection on T-Cell Dependent Humoral Immune Response - Rodriguez, Stéphane; Roussel, Mikaël; Tarte, Karin; Amé-Thomas, Patricia (Frontiers in Immunology, 2017)
During the last decades, considerable efforts have been done to decipher mechanisms supported by microorganisms or viruses involved in the development, differentiation and function of immune cells. Pathogens and their associated secretome as well as the continuous inflammation observed in chronic infection, are shaping both innate and adaptive immunity. Secondary lymphoid organs are functional structures ensuring the mounting of adaptive immune response against microorganisms and viruses. Inside these organs, germinal centers are the specialized sites where mature B cell differentiation occurs leading to the release of high affinity immunoglobulin-secreting cells . Different steps are critical to complete B cell differentiation process including proliferation, somatic hypermutations in immunoglobulin variable genes, affinity-based selection, and class switch recombination. All these steps require intense interactions with cognate CD4+ helper T cells belonging to follicular helper lineage. Interestingly, pathogens can disturb this subtle machinery affecting the classical adaptive immune response. In this review, we describe how viruses could act directly on germinal center B cells, either through B cell infection, or by their contribution to B-cell cancer development and maintenance. Additionally, we depict the indirect impact of viruses on B-cell response through infection of germinal center T cells and stromal cells, leading to immune response modulation.